DEVELOPING PERDASAWA (PERMAINAN DAKON AKSARA JAWA) MEDIAIN THE TEACHING OF JAVANESE ALPHABETSTO THE GRADE V STUDENTS OF ELEMENTRAY SCHOOLS - Ika Susianti; Arih Afra I.; Zidni Khasna T.; Fatma Khoirunisa; Imam Dwi U. (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
This research was aimed at developing Perdasawa media for the learning ofJavanesse alphabets for 5th graders.This research was classified as Research and Development. The data werecollected from the tests by media expert, subject expert, and personal test with the5th grade students.The research produced a media to learn Javanesse alphabets, namely a gamemedia. The form of the game media is wooden dakon which had 56 fiber kecik withJavanesse alphabets written on each of it. The Javanesse alphabets consisted of 25carikan letters, 20 couples of carikan letters, 11 sandhangan symbols, and were completedwith word cards whose function was to write the results of arranging the Javanessealphabets by the players.